PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) DAN PROBING-PROMPTING (PP) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DITINJAU DARI KEPERCAYAAN DIRI (SELF-CONFIDENCE) - Irvan Fariji (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2019)
The Influence of Problem-Based Learning (PBL) and Probing-Prompting (PP) Learning Models on Students' Critical Thinking Ability Judging from SelfConfidence. Mathematics Education Study Program, Postgraduate Program at Sultan Ageng Tirtayasa University. 2019. The purpose of this study was to describe influence of Problem-Based Learning and Probing-Prompting Learning Models on Students' Mathematical Critical Thinking Ability in the light of SelfConfidence. The low ability of students to think critically mathematically so that it is necessary to apply a learning model that trains students' thinking skills while fostering student confidence. The method used in this study is a quasiexperimental method that uses a 2x2 treatment by level design. Consideration of the use of this design is to see the answers to the research questions from two different treatments, namely: treatment of the learning model (A), and treatment of self-confidence (B) in the four treatment groups. The results revealed that students' mathematical critical thinking skills taught by PBL learning models were better than students taught with PP learning models had significant differences; Mathematical critical thinking ability of students who have high self-confidence is higher than students who have low self-confidence. The results of the study revealed that (1) There were differences in critical thinking skills between students learning using the problem-based learning (PBL) model and students learning to use probing-prompting (PP); (2) There are differences in critical thinking skills between students who have high self-confidence and students who learn to use students who have low self-confidence; (3) There is an interaction effect between the application of learning models and self confidence in students' critical thinking abilities; (4) There are differences in critical thinking skills between students who learn using the problem-based learning (PBL) learning model and high self-confidence (self confidence); and students who learn using probing-prompting (PP) learning models and high self confidence; (5) There are differences in critical thinking skills between students who learn using the problem-based learning (PBL) learning model and low self confidence; and students who study using probing-prompting (PP) learning models and low self confidence.Keywords: Problem-Based Learning, Probing-Prompting, Self-Confidence,Critical Thinking